Production and Purification of DNA G-quadruplex using pPH600 plasmid - Santos, Tiago André Afonso dos (2015)
When we think in structure of DNA, the image that comes immediately to mind is the iconic structure in double helix discovered by Watson and Crick in 1953. However, in addition to this structure DNA can assume other secondary structures which are relevant in the biological context. Some important regions of human genome have unusual potential to form this structures upon transcription. The plasmid pPH600 have a sequence of S?3 immunoglobulin switch region of murine that are able to form G-quadruplex upon transcription. The G-loops predominance is more evidenced on supercoiled (sc) topology than on relaxed (oc) or linearized (ln) plasmid. The present work describe the biosynthesis of plasmid pPH600 in E. coli DH5a and the strategies for sc pPH600 purification, directly from native sample (oc + sc) and clarified E. coli lysate. The purification strategies are based on amino acid affinity chromatography taking advantage of biological recognition to pDNA. For this propose two supports were prepared, L-tryptophan Sepharose and L-tyrosine Sepharose, by covalent immobilisation using 1,4-butanediol diglycidyl ether spacer arm. The commercial support L-arginine Sepharose 4B was also used in the strategy for purifying sc pPH600 since it has already been efficiently applied to separate sc isoforms of different plasmids using mild binding and elution conditions. Therefore, an initial screening with pPH600 native sample (oc + sc) was performed to evaluate the behavior of three supports. The better support in isoform separation was selected to purify sc pPH600 directly from clarified lysate. L-tyrosine support shows the prominent result in separation of two isoforms, allowing the recovery of sc pPH600, through a decreasing stepwise gradient from 2.25 to 0 M (NH4)2SO4 in 100 mM HEPES acid (pH 7.4) with temperature at 10ºC. Thereafter, the clarified E. coli lysate sample was injected directly onto L-tyrosine support to separate sc pPH600 from internal impurities of E. coli (gDNA, RNA, proteins, endotoxins and other conformations of pPH600). The total separation of sc pPH600 was totally achieved using a stepwise gradient from 2.25, 1.95 and 0 M (NH4)2SO4 in 100 mM HEPES acid (pH 7.4) with temperature at 10ºC. The underlying mechanism is thought to involve not only hydrophobic but also other non-covalent interactions such as, hydrogen bonds, p-p stacking and van der Waals interactions. Plasmid assessment tests indicated that the sc pPH600 resultant from the purification step presented a purity degree of 98.2%, with an extremely reduced level of impurities. Finally, the sc pPH600 resultant from purification was transcribed to induce the formation of G-quadruplex and it is confirmed by circular dichroism.